Experts vs. novices: applying eye-tracking methodologies in colonoscopy video screening for polyp search - Lacey, Gerard; Bernal, Jorge; Sánchez, Javier; Vilariño, Fernando; Arnold, Mirko; Ghosh, Anarta (ACM, 2014)
We present in this paper a novel study aiming at identifying the differences in visual search patterns between physicians of diverse levels of expertise during the screening of colonoscopy videos. Physicians were clustered into two groups -experts and novices- according to the number of procedures performed, and fixations were captured by an eye-tracker device during the task of polyp search in different video sequences. These fixations were integrated into heat maps, one for each cluster. The obtained maps were validated over a ground truth consisting of a mask of the polyp, and the comparison between experts and novices was performed by using metrics such as reaction time, dwelling time and energy concentration ratio. Experimental results show a statistically significant difference between experts and novices, and the obtained maps show to be a useful tool for the characterisation of the behaviour of each group.
Proceedings of the Symposium on Eye Tracking Research and Applications
Eye Tracking Research and Applications (ETRA)
Keywords: Saliency; Eye-tracking; Experts; Novices; Medical imaging; Polyp; Colonoscopy